Ética, justiça e direito: um olhar a partir do pensamento de Emmanuel Levinas - Lazzari, Artur (My University, 2019)
The present work is constituted in order to develop an approach on the possibility of a perspective of the right (or law) and the justice understood in the relation with the infinite present in the Other, oriented by an ethical view turned to take over responsibility before his otherness. The discussion here developed is necessary to face the large presence of the legal positivism in the practice of law, that in function of a certain impersonality in deal with facts and norms excuse itself from the ethical relation with that one that calls for justice. The ethical proposal of Emmanuel Levinas presents a view that recognizes the impossibility of apprehending infinity present in the person that presents itself before me, in that which infinitely Other. It is a proposal of primacy of ethical relationship in pursuit of a way out of ego self-centered domains. Therefore it comes at a first moment address the course of Levinas ethical primacy and the possibility of its experience, presenting and developing its core concepts for the research question, to then focus on the issue of the third and the justice in levinasian thought, establishing relation to a proposal of rights based on otherness, and at the end it's made a relationship between the developed discussions and Jacques Derrida perspective, linked to rights and justice, present in the text "Force of Law". The research is based on the hermeneutic method, in face mainly of a non totalizing interpretation over the levinasian thought. At the end stands out that the perspectives proposed by Levinas provide more than enough elements to a new view of right and justice, a view that support the non reduction of the Other to an element of comprehension. Thereby, it was not aimed come to a closed understanding of the discussed theme, the intent was much more on the way to develop of an overview upon those questions.
O presente trabalho se constitui no intuito de desenvolver uma abordagem sobre a possibilidade de uma perspectiva do direito e da justiça que se compreenda na relação com a infinitude presente no Outro, orientada por um olhar ético voltado para o assumir da responsabilidade diante de sua alteridade. A discussão aqui desenvolvida faz-se necessária face a larga presença do positivismo jurídico na prática do direito, que em função de uma certa impessoalidade no tratar dos fatos e das normas se exime da relação ética com aquele que apela por justiça. A proposta ética de Emmanuel Levinas apresenta um olhar que reconhece a impossibilidade de apreensão da infinitude presente na pessoa que se apresenta diante de mim, naquele que é infinitamente Outro. É uma proposta de primazia da relação ética na busca por uma saída dos domínios autocentrados do ego. Desse modo trata-se em um primeiro momento abordar o percurso do primado ético de Levinas e a possibilidade de sua experiência, apresentando e desenvolvendo seus conceitos centrais para a questão da pesquisa, para em seguida enfocar na questão do terceiro e da justiça no pensamento levinasiano, fazendo relação a uma proposta de direito pautado pela alteridade, e ao fim é feita uma relação entre as discussões desenvolvidas e a perspectiva de Jacques Derrida, ligada ao direito e à justiça, presente no texto “Força de Lei”. A pesquisa se baseia sobre o método hermenêutico, em face principalmente a uma interpretação não totalizante sobre o pensamento levinasiano. Ao fim destaca-se que as perspectivas propostas por Levinas fornecem elementos mais que suficientes a um novo olhar sobre o direito e a justiça, a um olhar que auxilie a não redução do Outro a um elemento de compreensão, e nesse sentido não se buscou chegar a um entendimento fechado sobre a temática discutida, o intuito se deu muito mais no sentido do desenvolvimento de um olhar sobre essas questões.
Keywords: Lévinas, Emmanuel, $d 1906-1995; Ética; Justiça; Direito; Ethics; Justice; Law